Imiquimod-induced CCR9 Ameliorates murine TNBS Colitis - Suzuki, Ryoma (Fukushima J Med Sci, 2016)
AIMS: To investigate whether Imiquimod (IMQ) as TLR7 ligand protects mice from colonic inflammation and the mechanisms underlying in such immunoregulatory conditions. METHODS: Murine colitis was induced to Balb/c mice by administration of trinitrobenzene sulfonic acid (TNBS) with or without daily intraperitoneal administration of IMQ. Colitis was evaluated by body weight decreases and by histological score. Also colonic mRNA expression was measured by RT-PCR. To confirm the induction of Regulatory T cells (Tregs) by type-1 IFN from pDCs, we generated mouse bone marrow-derived pDCs and co-cultured these with CD4(+) T cells isolated from mouse spleen with or without IMQ stimulation. Cytokine production in the culture supernatant was measured by ELISA and the number of Tregs were analyzed by flow cytometry. Spleen and mesenteric lymph nodes (MLN) from IMQ-treated mice were collected, and mRNA expressions of cytokine were measured by RT-PCR and cytokine productions were measured by ELISA. Tregs and chemokine expressions were analyzed in colon of TNBS-induced colitis mouse by immunohistochemistry. RESULTS: Administration of IMQ significantly suppressed colonic inflammation of TNBS-induced colitis. In the colons of IMQ-treated mice, mRNA expression of TNF-α was decreased, and strong expressions of IL-6, IFN-β and TGF-β were detected. IL-10 and TGF-β productions were increased in the supernatant of co-cultured cells stimulated with IMQ, although we were unable to detect Treg differentiaton in IMQ-stimulated co-cultured cells. In MLN of IMQ-treated mice, strong expressions of TLR7, IFN-β, TGF-β and Foxp3 mRNA were detected. IL-10 production from MLN cells was also increased in the IMQ-treated group. Finally, Tregs in the inflamed colon and CCR9 in MLN of IMQ-treated mice were detected. CONCLUSION: These results suggest that IMQ protects mice from TNBS colitis through induction of CCR9, which regulates accumulation of Tregs in the inflamed colon.